Geomagnetic spectrum unbiased by noise 8 to 60 days - Rangarajan, G.K. (My University, 1975)
Power spectral estimates unbiased by noise of horizontal intensity observations from three low and middle latitude stations, well separated from each other, in the period range 8 to 60 days are obtained adopting a procedure described by Black (1970). Results confirm that amplitudes at different frequencies exhibit latitudinal dependence. A significantly determined peak corresponding to a period of 13.9 days and absence of its sub harmonic near 28 days indicates the tendency for equi-distant spacing of solar active regions. Several other significant periodicities are also detected.
Keywords: Geomagnetic spectrum; Geomagnetic activity; Magnetic field; Noise